Forced displacement and behavioral change: an empirical study of returnee households in the Nuba Mountains - Abdel-Rahim, A.; Jaimovich, D.; Ylönen, A. (Defence and Peace Economics, 2018)
We use a unique data-set gathered during a short-lived interwar period in the Nuba Mountains of Sudan to compare characteristics of the households returning after the conflict with those that stayed in their communities of origin. We found that returning households seemed to face worse economic conditions, particularly in the case of female- headed returnee households. Nevertheless, our results show that returnees tend to perform better on different health indicators. Using a detailed set of variables about hygiene and sanitary habits, we explore the hypothesis that the latter result may be related to changes in attitudes given the distinct experiences during displacement. We show that returnees are indeed more likely to adopt these measures.